Gu Sui Bu (Drynaria fortunei J. Smith) prevents osteoporosis in ovariectomized rats by inhibiting pyroptosis through NLRP3/GSDMD/CASPASE-1 - Hui su; Jun Dong; Luyao Liu; Zechen Yan; Rujie Zhuang; Guangxin Huang; Haipeng Xue; Zhanwang Xu; Yu Pan (Pharmacological Research - Modern Chinese Medicine)
Traditional Chinese medicine Gu Sui Bu (Drynaria fortunei J. Smith), has the effect of tonifying the kidneys and strengthening bone. There are many modern studies on the anti-osteoporosis pharmacological mechanism of Gu Sui Bu (Drynaria fortunei J. Smith) but no reports on the pharmacological mechanism of Gu Sui Bu (Drynaria fortunei J. Smith) improving cell pyroptosis and anti-osteoporosis have been found. Aim: This study aims to verify the changes in cellular standard indicators in postmenopausal osteoporosis, thereby revealing the participating mechanism of pyroptosis and the intervention effect of Gu Sui Bu (Drynaria fortunei J. Smith) . Methods: Gu Sui Bu (Drynaria fortunei J. Smith) subjected to UHPLC-Q-Orbitrap-MS/MS analysis, and the OVX rat model was constructed in vivo as the research object. It was divided into sham operation group (SHAM), ovariectomized osteoporosis model group (OVX) and Gu Sui Bu (Drynaria fortunei J. Smith) group (TFRD-L, TFRD-H). After 3 months of modeling, the medication group was treated with Gu Sui Bu (Drynaria fortunei J. Smith) and the samples were collected after 12 weeks of intervention. ELISA was used to detect the levels of Caspase-1, NLRP3, GSDMD, IL-1β, and IL-18 in rat serum; the right femur was taken for Micro-CT large bone microstructure scanning and femoral BMD detection; the femur was subjected to rat histopathology HE, TRAP staining; immunohistochemistry and immunofluorescence staining of rat histopathology were performed. WB and PCR were used to observe the expression of Osteoblasts and pyroptosis-related indicators Caspase-1, NLRP3, GSDMD and RUNX2, IL-1β, and IL-18. Results: UHPLC-Q-Orbitrap-MS/MS analysis the main compounds in Gu Sui Bu (Drynaria fortunei J. Smith) samples were identified. These 9 chemical components are Palmitic acid, Fisetin, Caffeic acid, Naringin, Rutin, Uridine, Cafestol, Astilbin . Rat Micro-CT, The results of HE staining and TRAP showed that compared with the rats in the OVX group, the number of bone trabeculae in the rats in the Gu Sui Bu (Drynaria fortunei J. Smith) medication group (TFRD-L, TFRD-H) increased, became wider and thicker, and the bone density increased. Continuity increases and bone lacunae decrease. Rat serum ELISA, femoral tissue immunohistochemistry, immunofluorescence staining and WB, PCR showed that compared with the OVX group, Caspase-1, NLRP3, The expression levels of GSDMD and inflammation were reduced (p<0.05), and the expression of osteogenic marker RUNX2 was reduced and increased (p<0.05). Conclusion: The traditional Chinese medicine Gu Sui Bu (Drynaria fortunei J. Smith) can improve the bone density of ovariectomized osteoporosis model rats and significantly enhance the bone microstructure. At the same time, it reduced the expression of pyroptosis markers Caspase-1, NLRP3, and GSDMD in vivo, confirming that Gu Sui Bu (Drynaria fortunei J. Smith) may play an anti-osteoporosis effect through the NLRP3/GSDMD/Caspase-1 pathway.